2020
DOI: 10.1177/0046958020923537
|View full text |Cite
|
Sign up to set email alerts
|

Family-Centered Health Promotion: Perspectives for Engaging Families and Achieving Better Health Outcomes

Abstract: Communities and populations are comprised of individuals and families who together affect the health of the community. The family unit is an unparalleled player for maintaining health and preventing disease for public health because members may support and nurture one another through life stages. Preliminary research confirms that family-oriented health promotion and disease prevention are promising strategies because the family unit is both a resource and a priority group needing preventative and curative ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 41 publications
1
35
1
9
Order By: Relevance
“…When analysing the impact on primary prevention, this review has considered outcomes of participant-reported discussion of test results with others. In public health models, family-focused interventions for promotion of health and disease prevention are becoming increasingly recognised as a strategy towards greater, sustained health outcomes [37,38]. In the context of familial melanoma, the potential for a wider impact on primary prevention in relatives of high-risk individuals is particularly relevant for children of mutation carriers.…”
Section: Discussionmentioning
confidence: 99%
“…When analysing the impact on primary prevention, this review has considered outcomes of participant-reported discussion of test results with others. In public health models, family-focused interventions for promotion of health and disease prevention are becoming increasingly recognised as a strategy towards greater, sustained health outcomes [37,38]. In the context of familial melanoma, the potential for a wider impact on primary prevention in relatives of high-risk individuals is particularly relevant for children of mutation carriers.…”
Section: Discussionmentioning
confidence: 99%
“…A través de las guardias comunitaria programadas, diferentes servidores del establecimiento de salud de la jurisdicción, visitan a dichas familias y les brindan el soporte necesario al niño anémico para que este supere esta afección causada por la deficiencia de hierro en la sangre. Coincidimos con Barnes y colaboradores (18) quienes señalan que la promoción de la salud y la prevención de enfermedades orientadas a la familia son estrategias prometedoras porque la unidad familiar es tanto un recurso como un grupo prioritario que necesita servicios preventivos y curativos a lo largo de la vida.…”
Section: Discussionunclassified
“…Accordingly, health promotion activities must take place in the settings of people’s everyday lives, where they learn, work and play [ 3 ]. The family is a key setting to work with [ 4 ] and engaging parents in programs to increase children’s health and wellbeing can be an important strategy to situate these efforts in the context of everyday life [ 5 ]. Moreover, parenting and the quality of parent–child relationships are crucial factors determining the social and health development of children and youth [ 6 ], including children and young people’s cognitive development and educational outcomes [ 7 , 8 ], risk behavior [ 9 ], mental health [ 10 ], health and nutritional behavior [ 11 ] and mortality at all ages [ 12 ].…”
Section: Introductionmentioning
confidence: 99%